A rare case of progressive pseudorheumatoid dysplasia - Packia Stary, R. B. Grashia; Siromony, E. Nithin; Sylvia R., Karen (International Journal of Contemporary Pediatrics, 2022)
Progressive pseudorheumatoid dysplasia is a rare, autosomal recessive, noninflammatory musculoskeletal disorder caused by mutations occurring in the WNT1- protein present in 3 gene. Usual presentation is arthralgia, joint stiffness, contractures with primary involvement in joint cartilage. We present a 13-year-old female child presented with history of short stature, bowing of legs and curving of spine and inability to walk normally since the past two years. The symptoms have been progressively worsening for the past one year. Progressive pseudo rheumatoid dysplasia is a rare form of spondyloepimetaphyseal dysplasia and is clinically misdiagnosed as juvenile idiopathic arthritis. Any patient presenting with musculoskeletal symptoms should be evaluated appropriately to start appropriate therapy in time.